2023
DOI: 10.3389/fnut.2023.1107054
|View full text |Cite
|
Sign up to set email alerts
|

The metabolome of human milk is altered differentially by Holder pasteurization and high hydrostatic pressure processing

Abstract: The milk metabolome is composed of hundreds of molecules that can impact infant development. In preterm infants, sterilized donor milk (DM) is frequently used for their feeding. We aimed to identify differences in the metabolome of DM after two types of milk sterilization: the Holder pasteurization (HoP) and a high hydrostatic pressure (HP) processing. DM samples were sterilized by HoP (62.5°C for 30 min) or processed by HP (350 MPa at 38°C). 595 milk metabolites were analyzed using an untargeted metabolomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Sample collection, preparation, and the experimental design of the present study are shown in Figure 1. Sample size was estimated based on previous work (11)(12)(13)(14), common practice and G Power free software.…”
Section: Milk Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample collection, preparation, and the experimental design of the present study are shown in Figure 1. Sample size was estimated based on previous work (11)(12)(13)(14), common practice and G Power free software.…”
Section: Milk Collection and Processingmentioning
confidence: 99%
“…High hydrostatic pressure (HP) processing, a non-thermal method, has been proposed as an alternative to HoP for DM sterilization (10,12). Recently, it was demonstrated that using a moderate HP protocol (four cycles of 5 min at pressure of 350 MPa, performed at 38°C) numerous DM factors which are degraded by HoP are preserved by HP processing (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This thermal treatment is considered to be a good compromise between microbiological safety and the maintenance of the nutritional quality of DM. However, several studies have recently demonstrated that HoP reduces some nutritional compounds of DM [ 3 , 4 ]. In addition, it has been demonstrated that this pasteurization also degrades numerous heat-sensitive and bioactive factors, such as immunoglobulins, lactoferrin, some vitamins, lysozyme, the bile salt-dependent lipase (BSSL) and several important metabolic hormones [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has demonstrated that HHP may be one of the best innovative methods to sterilize DM, as this method maintains the nutritional value of DM as well as numerous bioactive compounds such as immunoglobulins, lactoferrin, lysozyme, BSSL enzyme, milk oligosaccharides and several hormones close to their initial levels (i.e., those found in raw milk) [ 5 , 7 , 10 , 11 ]. Recently, we have demonstrated that the use of a moderate HHP protocol (four cycles of 5 min at pressure of 350 MPa, performed at 38 °C) remarkably preserved these important milk compounds [ 4 , 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation